ANALISIS KESALAHAN PENERJEMAHAN KATA “MUST” PADA CERITA THE MIRROR DAN IMPLIKASINYA DALAMPEMBELAJARAN - Wahyuningsih, Agung Tri (Jurnal Pengembangan Pendidikan, 2010)
Abstrak. Translating is a hard work. It isnot only about finding the word of the source language (SL) having the samemeaning in the target language (TL). It talks about the message. Theword/phrase/sentence going to be translated is a text or it is called surfacestructure. A text needs context or known as deep structure which containsmessage. Therefore a word may have the same meaning either in SL or TL, butthey have different sense as they bring different message in different context.In this article, it is explored the mistranslation o the word “must”. Thisstudy observed 14 students who were learning English. They were asked totranslate a text entitled “The Mirror”. The analysis is focused on a paragraphconsisting of a word “must”. The result shows that the students are stillfocusing on the text or surface structure. They ignore the context or deepstructure. Thus, the message fails to be delivered.  Katakunci: translation, meaning, message,Source Language, Target Language.